2014
DOI: 10.20873/jbb.uft.cemaf.v5n2.braz
|View full text |Cite
|
Sign up to set email alerts
|

Resíduos da colheita florestal e do processamento da madeira na Amazônia – uma análise da cadeia produtiva

Abstract: O manejo sustentável da floresta Amazônica é de grande importância para a conservação do bioma, através da utilização racional dos seus recursos, sem levar a total destruição da mesma, minimizando os impactos ecológicos. Uma alternativa de atividade florestal sustentável é o aproveitamento dos resíduos da colheita florestal e do processamento mecânico da madeira. Resíduos oriundos da floresta são desperdiçados, muitas vezes em função de não saberem aproveitá-los ou por falta de opções tecnológicas. A fim de mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
15

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 9 publications
0
9
0
15
Order By: Relevance
“…Moreover, information on possible benefits of these residues and how they affect soil geochemical properties in managed areas of TDF-CPD is not found. However, the use of forest residues such as branches for energetic purposes have been studied for other natural and planted forests (BRAZ et al, 2014;CRUZ FILHO, SILVA, 2009), and benefits to soil have been found for pine plantations (WEBSTER et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, information on possible benefits of these residues and how they affect soil geochemical properties in managed areas of TDF-CPD is not found. However, the use of forest residues such as branches for energetic purposes have been studied for other natural and planted forests (BRAZ et al, 2014;CRUZ FILHO, SILVA, 2009), and benefits to soil have been found for pine plantations (WEBSTER et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Considerando que as perdas resultantes das operações de colheita são inerentes à atividade e nem sempre podem ser evitadas, o planejamento das mesmas devem ser inevitáveis priorizando a redução dos efeitos negativos gerados pelo desperdício sobre os custos de produção (ARCE, 2000). Esta questão também é discutida por Braz et al (2014), quando concordam que grande parte deste desperdício tem origem na ausência do planejamento, na implementação de novas tecnologias e na prática de técnicas adequadas.…”
Section: Rev Agrounclassified
“…No entanto, a falta de valor agregado de forma eficiente a este material traz impedimentos ao desenvolvimento de uma nova cadeia de produção, visto que o volume de resíduos florestais gerados é considerável (BRAZ et al, 2014). Outro ponto relevante é que muitos estudos realizados e publicados na literatura são relacionados ao aproveitamento de resíduos gerados na etapa do desdobro da madeira, ou seja, nas indústrias e não estão voltados para os resíduos gerados em campo pela ocasião da intervenção de colheita (PONTES et al, 2012).…”
Section: Introductionunclassified
“…In Amazonian sawmills low lumber yield is a common occurrence and is estimated at approximately 41% in a report presented by Hummel (Hummel et al, 2010). This creates economic and environmental problems because a greater volume of raw material must be consumed in order to compensate for the volume of wood lost (Braz et al, 2014). The Conama resolution Nº 474/2016 reduced to 35% the coefficient of volumetric yield for sawn wood with the goal of being more in sync with the realities faced by the sawmill industry in the region (BRASIL, 2016), thus sanctioning the low yield of lumber from raw material.…”
Section: Introductionmentioning
confidence: 99%